The antecedents and consequences of relationship quality of retail loyalty programmes / Nor Asiah Omar - Omar, Nor Asiah (2008)
Relationship quality has received increasing attention by researchers during the past decade. Research evidence has revealed that relationship quality has an influence on relationship outcomes such as customer loyalty, repurchase intention and word-of-mouth. Based on these reasons, relationship quality has received more overt emphasis by both academicians and practitioners. The data for this research were collected from 400 retail loyalty programme members in Malaysia via drop off and collect survey technique. Basically, this research had shed new light and understanding to the existing knowledge by incorporating various constructs in the antecedents of relationship quality such as perceived equity, programme perceived value, programme service quality, programme relationship orientation and member relationship proneness. The significance of the study lies in the fact that, it attempts to identify and empirically investigate the antecedents of relationship quality among programme members and in tum examines the consequences on member's behavioural loyalty such as program card loyalty and store loyalty in a retail loyalty programme setting. Structural Equation Modelling (SEM) was utilised to test the hypothesised relationships among the constructs, as postulated in the model. The results derived from the present study sheds new insights; firstly, the result exemplifies that ' courteousness/helpfulness' is the most important determinant of loyalty programme service quality (LoPQUAL). In turn, loyalty programme service quality is the most influential determinant of programme perceived value and programme satisfaction. Secondly, programme relationship orientation is the most important driver of programme trust, while programme trust is the most predictive indicator of programme commitment. Fourth, it was revealed that programme perceived value positively influenced perceived equity and which then found to be a significant predictor of programme commitment but not programme satisfaction. In terms of the consequences of relationship quality on behavioural loyalty (programme card loyalty and store loyalty), the results delineate several interesting findings; firstly, programme satisfaction and programme commitment holds a pre-eminent role in the formation of programme card loyalty and ultimately store loyalty However, programme satisfaction has no direct impact on store loyalty. Secondly, programme trust and programme commitment have significant direct impact on store loyalty. Thirdly, loyalty towards the programme is the most predictive determinant of store loyalty. Thus, this revealed that programme trust has an indirect effect on programme card loyalty mediated by programme commitment. And, programme satisfaction has an indirect effect on store loyalty mediated by programme card loyalty. Ultimately, the study's primary goal of developing a plausible model that has statistical and explanatory power, which could permit interpretation of results confidently, was achieved after a minor modification to the proposed model. Thus, the current research reveals three new links namely, member relationship proneness-programme card loyalty, perceived equity-programme card loyalty and programme card loyalty_store loyalty; that have not been examined empirically by previous research. Moreover, the research has also developed and validated a new measure called loyalty programme service quality (LoPQUAL), which attempts to offer a new dimension of loyalty programme service quality particularly in retail loyalty programme.